L’Autofiction comme Stratégie de Résistance dans Un Amour Impossible de Christine Angot: Autofiction as a Strategy of Resistance in Un Amour Impossible by Christine Angot - ODIBOH, Adenike Patience (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Many studies have investigated social norms and power structures through autofiction, particularly in the context of family and romantic relationships. But very little is known from Christine Angot’s perspective. This study examines the role of autofiction as a strategy of resistance in the latter’s novel Un Amour Impossible. The aim of this research is to analyze how Angot uses autofiction to challenge narrative and societal conventions, while expressing his own truth and reaffirming his identity. The methodology used is a detailed literary analysis of the novel to expose the autofiction techniques used by the author. The theoretical framework is based on the concepts of literary resistance and autofiction. Using feminist theory, this study examines how autofiction allows the author to deconstruct dominant narratives and reclaim their own narrative. The results reveal that the autofiction in the work allows the author to question social norms and claim an authentic voice, while exposing the power dynamics that underlie family and romantic relationships. Furthermore, the study shows that autofiction in Angot serves to redefine the notion of identity and personal memory, which offers an incisive critique of patriarchal structures and societal expectations. This study contributes to enrich discussions on self-expression in contemporary literature, while highlighting the importance of autofiction as a tool of resistance and social transformation.